2003
DOI: 10.1186/1472-6920-3-3
|View full text |Cite
|
Sign up to set email alerts
|

Long-term follow up of factual knowledge after a single, randomised problem-based learning course

Abstract: Background: The long-term effect of problem-based learning (PBL) on factual knowledge is poorly investigated. We took advantage of a previous randomised comparison between PBL and traditional teaching in a 3 rd year course to follow up factual knowledge of the students during their 4 th and 5 th year of medical school training.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 10 publications
1
6
0
Order By: Relevance
“…Some have suggested that knowledge brokering is a long and involved process [107-109]. It addition to the explanations provided earlier, it is also possible that the duration and intensity of the KB intervention was insufficient to facilitate significant changes in evidence-informed decision making.…”
Section: Discussionmentioning
confidence: 99%
“…Some have suggested that knowledge brokering is a long and involved process [107-109]. It addition to the explanations provided earlier, it is also possible that the duration and intensity of the KB intervention was insufficient to facilitate significant changes in evidence-informed decision making.…”
Section: Discussionmentioning
confidence: 99%
“…However, the conclusion drawn from these studies indicated positive effects [4][5][6][7][8][9] or, otherwise, neutral effects of the PBL method. [10][11][12][13] PBL was first implemented in dental classes at the Harvard School of Dental Medicine (HSDM) in fall 1994. The HSDM predoctoral curriculum has transitioned from a traditional curriculum to a PBLhybrid curriculum in both preclinical and clinical education, with an expectation that this pedagogy would enhance the students' critical and interdisciplinary thinking and communication skills as well as their general professional competencies.…”
mentioning
confidence: 99%
“…If the introduction of a PBL curriculum has no clear effect on the selection of pathology as a career, this should come as no surprise given that PBL appears to have had similarly minimal results on a variety of outcomes. Whether the measure is standardized certification examinations [9,[12][13][14][15][16], course examinations [17][18][19], clerkship evaluations [20], or student self-perception of knowledge [19], in general there appears to be minimal or no difference between medical students which can be independently attributed to PBL versus non-PBL instruction.…”
Section: Discussionmentioning
confidence: 99%